2003
DOI: 10.1086/368149
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Infrared Synchrotron Radiation from Cassiopeia A

Abstract: We report the discovery of polarized flux at 2.2 micron from the bright shell of the approximately 320 year old supernova remnant Cas A. The fractional polarizations are comparable at 6 cm and 2.2 micron, and the polarization angles are similar, demonstrating that synchrotron radiation from the same relativistic plasma is being observed at these widely separated wavebands. The relativistic electrons radiating at 2.2 micron have an energy of ~ 150 GeV, (gamma ~ 3e5), assuming an ~500 microGauss magnetic field. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 52 publications
5
39
0
Order By: Relevance
“…The cut-off energy ǫ, the normalization of the spectrum and the value of an interstellar absorption column were allowed to be free parameters. We froze the curvature parameter to a value of 0.06 based on fits to radio and infrared synchrotron data for selected regions of Cas A [38]. A value 5 of a = 0.05 was obtained by our group in fits to SN1006 [39].…”
Section: Creating a Cut-off Frequency Mapmentioning
confidence: 99%
“…The cut-off energy ǫ, the normalization of the spectrum and the value of an interstellar absorption column were allowed to be free parameters. We froze the curvature parameter to a value of 0.06 based on fits to radio and infrared synchrotron data for selected regions of Cas A [38]. A value 5 of a = 0.05 was obtained by our group in fits to SN1006 [39].…”
Section: Creating a Cut-off Frequency Mapmentioning
confidence: 99%
“…This theory has been tested and confirmed for the Tycho and Kepler SNRs by Reynolds & Ellison (1992). Very recently Jones et al (2003) reported that infrared observations of Cas A also indicate a flattening of the synchrotron spectrum at high frequencies.…”
Section: Cosmic Ray Acceleration and X-ray Synchrotron Emission From mentioning
confidence: 71%
“…A concavity in the spectrum of the radiation generated by relativistic electrons appears to be one of the possible evidences for shock acceleration in the non-linear regime. In the case of supernova remnants, there are hints that this concavity might have been observed [32].…”
Section: Discussion and General Remarksmentioning
confidence: 99%